(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to identify the cognitive aspects of the research variables and verify the impact of electronic governance on financial control. These variables were studied in a sample of employees in the banking field in Iraqi commercial banks listed on the Iraq Stock Exchange, and after determining the percentage by the statistician, which numbered (12). ) bank, and the sample included (127) individuals distributed at several administrative levels, and by adopting the questionnaire that included (30) items as the main tool for collecting data, the researchers adopted the descriptive and analytical approach, and used many statistical methods, namely the arithmetic mean and the standard deviation, and the researchers reached conclusions that were The most important of which is the existence of a significant impact of electronic governance on financial control procedures. Some private banks apply some components of electronic banking services, but they need more attention through automated teller machines (ATM), as well as providing bank cards and online exchanges to strengthen relations with... customers, and the researchers reached recommendations, the most important of which were preparing future plans and programs to activate the application of electronic governance for its role in improving banking performance, regularly evaluating financial control procedures in units that use electronic governance to identify weak points and developing appropriate procedures to address them. The infrastructure should be developed in support of electronic governance requirements. To operate successfully, this is achieved by providing effective communication systems for the transfer and flow of data and information between banks, citizens, business institutions and subsidiary institutions.